The Association between Relative Risk and Risk Estimates Derived from Quarterly Earnings and Dividends. - Griffin, Paul A. (The Accounting Review, 1976)
Abstract The purpose of this study is to examine two effects of quarterly earnings and dividend information, the association between a measure of relative risk and risk estimates derived from quarterly earnings and quarterly dividends and the extent to which significant differences exist between associations when the combined earnings and dividend risk measures are classified dichotomously as either unambiguous or ambiguous in their implications of the assessment of relative risk. The dichotomous classification procedure is outlined in a subsequent section. A knowledge of both effects is of importance to investors, firm managers and independent accountants. Evidence that a positive association exists between a firm's relative risk and quarterly earnings and dividends suggests that information pertinent to the value of a firm may be ascribed to these numbers. Indeed, since they may constitute a subset of the broad information set used to assess levels of risk and risk changes, the evidence may be of direct benefit for the establishment of efficient capital market resource allocations. The U.S. Securities and Exchange Commission also has recognized a need for examination of the utility of quarterly corporate financial statements.